Genetics of pain: From rare Mendelian disorders to genetic predisposition to pain - Naureen, Zakira; Lorusso, Lorenzo; Manganotti, Paolo; Caruso, Paola; Mazzon, Giulia; Cecchin, Stefano; Marceddu, Giuseppe; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Pain is defined by the International Association for the Study of Pain as “an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage”. In this mini-review, we focused on the Mendelian disorders with chronic pain as the main characteristic or where pain perception is disrupted, and on the polymorphisms that can impart susceptibility to chronic pain. Methods: We searched PubMed and Online Mendelian Inheritance in Man (OMIM) databases and selected only syndromes in which pain or insensitivity to pain were among the main characteristics. Polymorphisms were selected from the database GWAS catalog (https://www.ebi.ac.uk/gwas/home). Results: We retrieved a total of 28 genes associated with Mendelian inheritance in which pain or insensitivity to pain were the main characteristics and 70 polymorphisms associated with modulation of pain perception. Conclusions: This mini-review highlights the importance of genetics in phenotypes characterized by chronic pain or pain insensitivity. We think that an effective genetic test should analyze all genes associated with Mendelian pain disorders and all SNPs that can increase the risk of pain.